Perfil socioeconômico dos ovinocultores e aspectos ambientais da criação de ovinos de corte dos municípios de Santarém e Mojuí dos Campos, Pará, Brasil - QUEIROZ, Angela Cira Lima de (Universidade Federal do Oeste do Pará, 2023)
This study was divided into two chapters, the first deals with a literature review and the second with the profile of sheep breeders, aiming to describe the socioeconomic profile of sheep farmers and the environmental profile of sheep breeding in the municipalities of Santarém and Mojuí dos Campos. The study was carried out in sheep farming communities in rural areas and covered the population of sheep producers with family properties in the municipalities of Santarém and Mojuí dos Campos, which are registered at Emater (Company of Technical Assistance and Rural Extension) or at SIRSAN (Rural Union of Santarém), or in the STTR (union of rural workers of Santarém). This research was carried out on a descriptive and exploratory basis, being carried out through an on-site interview in March 2023. The questionnaire was semi-structured with open and closed questions., in which it collected data from 21 sheep producers. After obtaining the collected data, these were tabulated, and the analysis was performed using descriptive statistics, exposing absolute and relative values. The socioeconomic profile of the participants showed that 19 (90.47%) were men, with heterogeneous ages, complete higher education (52.38%), do not participate in social programs (100%) and raise sheep for family influence (61, 90%). When questioned about the use of beef sheep farming as a source of income, 61.90% reported yes, and the others reported the creation as an alternative option, but not as a source of income. When asked about how to use the production, 52.38% stated that they have the family habit of consuming sheep meat and viscera and the others sell the meat of these animals. The most used production system in the properties was the semi-intensive (81%). In relation to the type of practice implemented within the properties, only 28.57% use the integrated crop, livestock, forest system. Regarding the main diseases in sheep farming, it was possible to observe that 39.21% of them are associated with worm problems, followed by hoof problems (31.38%). The highest cost of diseases was caused by worms, with an annual average of R$207,25. For the environmental parameters, it was noted that the declivity in the land where the sheep are raised is mostly flat (71%), and in none of these were evidenced the presence of eroded soil (100%). Regarding the use of conservation or APP use, 47.61% reported that they adopt areas without native vegetation cover and included in the production system, followed by the use of native forest area with partial use in the production system (23.80%). As for the manure produced on the properties, it was possible to observe that most breeders (71.42%) let the manure tan and then deposit it in the pasture. It is concluded that sheep breeders are made up of men, aged between 45 and 54 years, with higher education, who do not participate in social programs and raise sheep for family influence. Few sheep farmers carry out sustainable and sanitary practices, which causes greater financial expenses and can cause damage to the environment.